An Electronic Wave Laboratory Worksheet Integrating Virtual Simulation and Performance Assessment - Latifah, Sri; Diani, Rahma; Yuberti, Yuberti; Rifai, M. (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2026)
Virtual laboratory technologies have expanded opportunities for interactive physics practicum learning; however, existing electronic laboratory worksheets rarely combine simulation-based experimentation, structured laboratory guidance, and authentic performance assessment within a unified instructional resource. This study developed and evaluated an electronic wave laboratory worksheet that integrates virtual simulation with embedded performance assessment to support higher education physics practicum. A research and development approach based on the ADDIE model was employed, encompassing analysis, design, development, implementation, and evaluation. The worksheet was designed using Crocodile Physics to facilitate concept visualization, guided experimentation, and systematic practicum activities. Product quality was examined through expert review, while its practicality was evaluated through feedback from university students and physics educators at two higher education institutions. The findings indicate that the worksheet demonstrated high validity and was perceived as practical, engaging, and suitable for supporting simulation-based laboratory learning. By integrating interactive simulation, structured experimental guidance, and authentic performance assessment, the worksheet enables students to visualize wave phenomena, conduct virtual investigations, and demonstrate practical competencies within a coherent learning environment. This study contributes an integrated instructional framework for technology-enhanced physics laboratory learning and offers practical guidance for designing simulation-supported practicum resources that promote authentic assessment in higher education.